(untitled) (The Review of Diabetic Studies, 2024)
Background Medication coordination between pharmacists and nurses ensures accurate, safe medication therapy across care continuums, addressing polypharmacy, transitions, and errors in diverse settings amid aging populations and complex pharmacotherapy.​ Methods This review systematically synthesizes empirical studies (quantitative, qualitative, mixed-methods) and reviews on pharmacist-nurse collaboration in medication management, using guiding questions on models, outcomes, and barriers across acute, primary, community, and long-term care settings.​ Results Coordination reduces medication discrepancies (e.g., 40% in hospitals), adverse events, readmissions, and improves adherence, disease control, workflow efficiency via models like ward-embedded pharmacists, reconciliation, and shared tools; barriers include communication gaps, role ambiguity, workloads.​ Conclusions Strengthening pharmacist-nurse partnerships through education, standardized processes, technology, and policy enhances safety and outcomes; future research needs longitudinal trials and global comparisons.​